Dimensi Spiritualitas Sufistik Ahmad Ibn Idris: Pengaruh dan Relevansi di Era Kontemporer - Syawaluddin Nasution; Qori Ananda Azhari Hasibuan; Azrin Eka Putra (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2024)
This paper explores the dimension of spirituality in the thought of Ahmad Ibn Idris and its relevance for contemporary life. Ahmad Ibn Idris, a prominent Sufi scholar, offers a profound spiritual perspective, inviting humans to establish a more intimate relationship with the Creator. Through a qualitative approach, this study reveals Ibn Idris' teachings and emphasizes their importance in facing modern challenges such as moral crises and social alienation. This research employs a qualitative methodology, combining historical analysis and interpretative methods to examine the writings and teachings of Ahmad Ibn Idris. Primary sources, including Ibn Idris' manuscripts and recorded teachings, are analyzed to understand his spiritual doctrines. Secondary sources, such as scholarly articles and books on Ibn Idris and Sufism, are reviewed to provide context and support the analysis. The study also incorporates thematic analysis to identify and categorize key themes in Ibn Idris' teachings related to spirituality, morality, and social cohesion. The findings suggest that Ibn Idris' teachings not only have historical value but also provide practical solutions that can be integrated into modern life to address various existing social and moral challenges. This research indicates that the teachings of Ibn Idris are relevant as a means to achieve balance and harmony in life. It contributes to the literature on contemporary Islam and spirituality, offering new insights into the integration of spiritual values in modern life. The study invites reflection and integration of spiritual dimensions as an answer to the search for the meaning of life in the contemporary era